2020
DOI: 10.1101/2020.09.17.300996
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Monocytes and macrophages, targets of SARS-CoV-2: the clue for Covid-19 immunoparalysis

Abstract: To date, the Covid-19 pandemic affected more than 18 million individuals and caused more than 690, 000 deaths. Its clinical expression is pleiomorphic and severity is related to age and comorbidities such as diabetes and hypertension. The pathophysiology of the disease relies on aberrant activation of immune system and lymphopenia that has been recognized as a prognosis marker. We wondered if the myeloid compartment was affected in Covid-19 and if monocytes and macrophages could be infected by SARS-CoV-2. We s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
58
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 40 publications
(21 reference statements)
13
58
3
1
Order By: Relevance
“…For example, DEGs observed from NP swabs showed high correlation to tissue specific DEGs in the early stages of infection, but very little correlation later infection. To explain this phenotype, recent evidence has suggested that monocytes can migrate into tissues as the SARS-CoV-2 infection progresses 15 , and this response can potentially explain the different correlations. It has also been reported that monocyte depletion/migration is associated with kidney disease, inducing lupus like symptoms 16 , which could potentially explain the correlation with kidney tissue.…”
Section: Discussionmentioning
confidence: 99%
“…For example, DEGs observed from NP swabs showed high correlation to tissue specific DEGs in the early stages of infection, but very little correlation later infection. To explain this phenotype, recent evidence has suggested that monocytes can migrate into tissues as the SARS-CoV-2 infection progresses 15 , and this response can potentially explain the different correlations. It has also been reported that monocyte depletion/migration is associated with kidney disease, inducing lupus like symptoms 16 , which could potentially explain the correlation with kidney tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, monocytes express ACE2 [ 184 ] and are permissive for SARS-CoV-1 [ 186 ], suggesting that they may also be susceptible to SARS-CoV-2 infection. To date, only abortive infection of SARS-CoV-2 has been described in monocytes and monocyte-derived macrophages [ 187 , 188 ]. Non-productive monocyte/macrophage infection by SARS-CoV-2 is also associated with production of immunoregulatory cytokines (IL-6, IL-10, IFN-α, IFN-β, IL-1) [ 187 , 188 ], which were shown to induce infected cell apoptosis via IFN-α/β receptor engagement [ 188 ].…”
Section: Consequences Of Endothelium Dysfunction In Covid-19mentioning
confidence: 99%
“…To date, only abortive infection of SARS-CoV-2 has been described in monocytes and monocyte-derived macrophages [ 187 , 188 ]. Non-productive monocyte/macrophage infection by SARS-CoV-2 is also associated with production of immunoregulatory cytokines (IL-6, IL-10, IFN-α, IFN-β, IL-1) [ 187 , 188 ], which were shown to induce infected cell apoptosis via IFN-α/β receptor engagement [ 188 ]. It is therefore possible that abortive infection of monocytes/macrophages impairs the antiviral response against SARS-CoV-2 and contributes to disease progression [ 187 , 188 ].…”
Section: Consequences Of Endothelium Dysfunction In Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Boumaza et al showed in vitro that SARS-CoV-2 efficiently infects monocytes and macrophages, which resulted in the secretion of TGF-b. 32 There are no reports though that show that this occurs in COVID-19 patients. In an additional study, TGF-b1 was increased in two different subsets of CD4 + immune cells of the COVID-19 patient group compared to the healthy control group.…”
Section: Involvement Of Tgf-b In Different Pathogenesesmentioning
confidence: 99%